Evaluation of Worker Discomfort on Manual Palletization Activities of Bottled Water Products - Firstama Saka Adiatmaja; Guntarti Tatik Mulyati; Didik Purwadi (Agroindustrial Journal, 2022)
The risk of Musculoskeletal Disorders (MSDs) is one of the problems that often occurs in manual handling workers with heavy loads in repetitive work movements for a long time. One example of this movement is the manual palletization activity of Bottled Drinking Water products at PT XYZ. Initial observations showed that 18 workers felt limb discomfort while stacking cardboards of 18kg water bottles. This study aims to determine the Recommended Weight Limit (RWL) used to measure the lifting load limit for workers; Lifting Index (LI) measurement that can describe the level of safety of lifting loads.The results showed that the load limit in drinking water palletization activities exceeded RWL, while the results of the LI calculation showed that manual palletization activities of bottled drinking water had a score of 6.4 where the LI score according to the safety standards of lifting activities was 1. These results indicate that manual palletization activities are not safe for workers and are at risk of causing MSDs. This is evidenced by the results of the assessment of the level of work posture discomfort using NBM which shows the highest pain score in the lower back of the body. Furthermore, workload measurement results vary from heavy to very heavy. From all parameters measured, it can be seen that the manual palletization activity of Bottled Drinking Water products at PT XYZ is very poor. The recommendation that can be proposed is to change the work system of manual palletization activities to a mechanical or automatic system.